CLOSEDNESS EQUATION FOR BIORTHOGONAL SYSTEM OF FUNCTIONS - Nikolay A. Bazarenko; Isa M. Peshkhoyev (Advanced Engineering Research)
Closedness  equation for biorthogonal system of functions has been derived. Closed-loop function systems characteristics are defined. They allow to solve contact problems of elasticity theory for finite bodies – a rectangle, a circular plate, a cylinder of finite length, etc.